Control of Host Cell Phosphorylation by Legionella Pneumophila - Haenssler, Eva; Isberg, Ralph R. (Frontiers in Microbiology, 2011)
Phosphorylation is one of the most frequent modifications in intracellular signaling and is implicated in many processes ranging from transcriptional control to signal transduction in innate immunity. Many pathogens modulate host cell phosphorylation pathways to promote growth and establish an infectious disease. The intracellular pathogen L. pneumophila targets and exploits the host phosphorylation system throughout the infection cycle as part of its strategy to establish an environment beneficial for replication. Key to this manipulation is the L. pneumophila Icm/Dot type IV secretion system, which translocates bacterial proteins into the host cytosol that can act directly on phosphorylation cascades. This review will focus on the different stages of L. pneumophila infection, in which host kinases and phosphatases contribute to infection of the host cell and promote intracellular survival of the pathogen. This includes the involvement of phosphatidylinositol 3-kinases during phagocytosis as well as the role of phosphoinositide metabolism during the establishment of the replication vacuole. Furthermore, L. pneumophila infection modulates the NF-κB and MAPK pathways, two signaling pathways that are central to the host innate immune response and involved in regulation of host cell survival. Therefore, L. pneumophila infection manipulates host cell signal transduction by phosphorylation at multiple levels.